Student Satisfaction with Frontline Services at a Philippine State University - Ubat, Joel; Villalon, Guadiosa (Journal of Interdisciplinary Perspectives, 2024)
This study investigated student satisfaction with the frontline services provided by a Philippine state university, including canteen, academic advising, counseling, library services, registration process, and campus facilities. The goal is to identify the strengths and weaknesses of these services from the student's perspective and provide insights for improvement. A quantitative approach was employed, using a survey questionnaire as the primary data collection tool. The findings reveal that students are generally highly satisfied with the frontline services. The Security Management Office and Student Affairs Office received the highest average weighted mean of 4.44, indicating strong satisfaction. Conversely, the Campus Canteen received the lowest average weighted mean of 4.32, suggesting comparatively lower satisfaction. Respondents also provided suggestions for improvement, such as increasing space for accommodations and waiting areas. This study contributes to understanding students' perceptions and experiences with frontline services at the state university. By identifying areas of strength and weakness, the results can guide the administration and relevant departments in enhancing service quality, thereby improving overall student satisfaction. Additionally, the study serves as a baseline for future research and provides a framework for evaluating the effectiveness of implemented improvements.